Improving Student Ability in Writing Narrative Text by using Silent Cartoon Animation - Dewi, Si Putu Agung Ayu Pertiwi; Purwaningsih, Ni Komang; Lindawati, Ni Putu (Indonesian literature Program, Faculty of Humanities, Diponegoro University, 2022)
Writing is one of the skills that must be improved. Writing requires complex skills such as developing creative ideas, vocabulary variations and also using good and correct grammar. This is because most students lack vocabulary, find it difficult to generate ideas in writing and are less able to string words together in writing. One of the efforts to improve writing skills is through the presentation of Silent Cartoon Animation in Narrative Text writing. The purpose of this study is to improve the ability to write narrative texts by using silent cartoon animation in an effort to provide a stimulus to students so that they can come up with ideas that can be put into written form. This research uses the classroom action research (CAR) method which examines quantitative and qualitative data from the applied linguistic aspect. Based on the results of the study, it was found that the use of Silent Cartoon Animation media was able to improve students' abilities in writing narrative text.